Timing of Immune Escape Linked to Success or Failure of Vaccination - Reece, Jeanette C. (Public Library of Science, 2010)
Successful vaccination against HIV should limit viral replication sufficiently to prevent the emergence of viral immune escape mutations. Broadly directed immunity is likely to be required to limit opportunities for immune escape variants to flourish. We studied the emergence of an SIV Gag cytotoxic T cell immune escape variant in pigtail macaques expressing the Mane-A*10 MHC I allele using a quantitative RT-PCR to measure viral loads of escape and wild type variants. Animals receiving whole Gag expressing vaccines completely controlled an SIV(mac251) challenge, had broader CTL responses and exhibited minimal CTL escape. In contrast, animals vaccinated with only a single CTL epitope and challenged with the same SIV(mac251) stock had high levels of viral replication and rapid CTL escape. Unvaccinated naïve animals exhibited a slower emergence of immune escape variants. Thus narrowly directed vaccination against a single epitope resulted in rapid immune escape and viral levels equivalent to that of naïve unvaccinated animals. These results emphasize the importance of inducing broadly directed HIV-specific immunity that effectively quashes early viral replication and limits the generation of immune escape variants. This has important implications for the selection of HIV vaccines for expanded human trials.